Human Capital and Banking Performance in Pakistan: The Moderating Role of Income Diversification - Ameenullah Aman; Umair Wahab (Social Science Review Archives, 2025)
The purpose of the paper is to study the impact of human capital on Islamic and conventional banks performance in Pakistan. The study uses the sample of 10 Islamic and conventional banks and panel data for the years 2011-2020. The hypothesis are tested through pooled OlS test and the choice between fixed effect and pool OLS estimation is based on results of Breusch and Pagan Lagrangian multiplier test and Hausman test. The study examined that human capital significantly have negative impact on bank performance. While income diversification has also significantly negative effect on bank performance. Additionally, interaction variable has significant and negative effect on bank performance, conclude that income diversification has an opposite effect on human capital and bank performance relation. For control variables asset quality liquidity, bank capitalization has significantly negative effected bank performance. The study serve as a helping hand for the policy makers and practitioners regulating the banking industry in Pakistan as it will give them an in-depth insight and understanding of the moderating effect of income diversification on human capital as well as individual impact of human capital, bank capitalization, asset quality, and liquidity and income diversification on the performance of Islamic and conventional banking system of Pakistan.